IFRS adoption in one Norwegian and one Russian bank : a comparative study - Kulikov, Mikhail (Høgskolen i Bodø, 2008)
Mastergradsoppgave i bedriftsøkonomi - Høgskolen i Bodø, 2008 International Financial Reporting Standards (IFRS) have become an integral part of the global financial environment and Russia and Norway now is no exception to this global trend. The present research seeks: · To describe differences/similarities of IFRS adoption in one Norwegian and one Russian Bank, · To analyze these differences based on accounting and institutional theory, · To understand challenges of IFRS adoption. The case study for the present research is one Norwegian and one Russian bank, which became partners recently. Interviews with employees are viewed as major tool of data gathering. A theoretical framework driven by Miller's theory and an institutional approach is elaborated. The present research shows that the forced introduction of IFRS has lead to a wide range of consequences depended on initial accounting traditions. In case of Norway, idea of IFRS introduction was presented in hierarchical and proactive way. This resulted in quick and full compliance to IFRS. In case of Russia, global idea of IFRS was introduced in hierarchical and reactive way. As a consequence there is long reforming in time (app. 10 years), characterizing by both parameters: “continuity” and “change”. The main differences stem from different initial accounting traditions. IFRS can be seen as a language between different national accounting practices, but one should take into account that big differences in initial accounting traditions may prevent IFRS to carry out that function. In case of Norway and Russia, IFRS can be a language of business cooperation, but there is a need for necessity and competence improvement in Russia. The research finally reveals limitations of the study and gives implications for further research.